Partnerships and Local Initiatiatives: Pillars of Inclusive and Sustainable Food Security - Adzkiyah, Tsabitha Mahda (Program Studi Ilmu Ekonomi UIN Sunan Ampel Surabaya, 2025)
Food security is an important pillar of inclusive and sustainable development, especially in the face of global challenges such as climate change, urbanization and social inequality. This article aims to highlight the importance of partnerships and community empowerment as key strategies in strengthening food security in Indonesia. Through a collaborative approach involving the government, private sector, non-governmental organizations and local communities, a more holistic and sustainable solution can be created. The research method used is a literature study and policy analysis focusing on partnership practices and local initiatives in the context of food security. The results show that partnerships involving various parties can increase agricultural productivity, access to food, and strengthen the local economy. In addition, community empowerment through education, access to resources and strengthening local capacity has proven effective in creating a more resilient food system. In conclusion, collaboration between various parties with an inclusive approach is key to achieving sustainable food security. Through strong partnerships and community empowerment, food security can be strengthened, thereby contributing to sustainable development goals such as poverty alleviation and environmental conservation